2001
DOI: 10.2135/cropsci2001.1850
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Soybean with Soybean mosaic virus Increases Susceptibility to Phomopsis spp. Seed Infection

Abstract: Infection of soybean [Glycine max (L.) Merr.] plants with Soybean mosaic virus (SMV) has been reported to enhance Phomopsis spp. seed infection, which reduces seed quality. The objective of this study was to determine the influence of SMV on Phomopsis spp. seed infection and seed germination and vigor. During 1995 to 1997, plants of two SMV‐susceptible cultivars (Clark and Williams) and their SMV‐resistant isolines (L78‐434 and L78‐379, resistant to SMV strains G1‐G6) were mechanically inoculated with SMV (G2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Phomopsis seed infection tends to be higher in BPMV-infected soybean plants (1,85). SMV infection also increases Phomopsis seed infection (40). Seed infection by Phomopsis occurs during the R7 and R8 growth stages, when pod and seed moisture decline.…”
Section: Impact Of Bpmv Infection On Soybeanmentioning
confidence: 97%
“…Phomopsis seed infection tends to be higher in BPMV-infected soybean plants (1,85). SMV infection also increases Phomopsis seed infection (40). Seed infection by Phomopsis occurs during the R7 and R8 growth stages, when pod and seed moisture decline.…”
Section: Impact Of Bpmv Infection On Soybeanmentioning
confidence: 97%
“…Similar results were reported by Stuckey et al (32), who reported that SMV had no effect on seed infection by Phomopsis spp. In previous studies, only highly virulent SMV isolates caused an increase in seed infection by Phomopsis spp., and the effect differed among cultivars (8,15,16). only in plants co-infected with SMV and BPMV.…”
Section: Discussionmentioning
confidence: 92%
“…Koning et al (16) observed a significant increase in seed infection by Phomopsis spp. due to inoculations with a SMV-G2 strain, which was likely to cause an extension of the seed development interval in SMV-susceptible cultivars.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations